The Role of Telemedicine in Enhancing Surgical Care Delivery in Africa: A Literature Review - Alicia Kwan Su Huey; Aman Singh Sengar; Zeinab Kazan; Karan Choudhary; Raj Pravin Patel; Magda Wojtara; Olivier Uwishema (Health Science Reports)
ABSTRACT Background and Aims In Africa, telemedicine holds great potential to revolutionize surgical care delivery, especially in areas where access to quality treatment is scarce. Data about the use of these services in African countries is, however, limited. To outline the present issues in surgical care delivery, as well as the significant role of telemedicine in advancing surgical care delivery in Africa. This review will also discuss the challenges behind telemedicine utilization in Africa, and recommend targeted measures to address those barriers while promoting the enhanced integration of telemedicine into surgical care delivery. Methods A comprehensive online literature search was conducted using several search engines, including PubMed, ScienceDirect, and Google Scholar to assess the potential advantages of telemedicine over traditional surgical practices in Africa, as well as to identify the challenges hindering its implementation. The literature review examined the role of nongovernmental organizations in promoting telemedicine adoption across various African countries. Literature search terms include “countries of Africa,” “impact of telesurgery and telemedicine in Africa,” and “current situation of telemedicine in intervention.” Only articles written in English were considered, and inclusion criteria included relevance to our research objectives and countries in Africa. Results The potential for telesurgery in Saharan and sub‐Saharan countries is still a milestone to be unlocked, but already telemedicine implementation has shown great results. Although hindrances like trust, lack of infrastructure, and lack of trained personnel in the field of telecommunication have been issues. There is a rise in the use of telemedicine in areas of interest like postsurgical care, doctor‐patient consultation, and tele‐monitoring. Various schemes and plans implemented by public organizations have also peaked since the pandemic. A telemedicine establishment requires multifactorial development occurring in a step‐by‐step manner. Although complexity in development and barriers faced in countries in Africa are concerns, the outcomes of using telemedicine are considerably better. The rising population and lack of medical specialists have led to a gap in access to approachable surgical care, and telemedicine has shown promising potential to overcome it. Conclusion Telemedicine implementation has changed the method of intervention in clinics all over the world. Implementation of parts of telemedicine like telesurgery and tele‐monitoring has the potential to overcome the concern of a rising population, but there is still a long way to go.